Integrated care for resected early stage lung cancer: innovations and exploring patient needs. Issue 1 (12th June 2017) - Ho, Jan; McWilliams, Annette; Emery, Jon; Saunders, Christobel; Reid, Christopher; Robinson, Suzanne; Brims, Fraser
Abstract : There is no consensus as to the duration and nature of follow-up following surgical resection with curative intent of lung cancer. The integration of cancer follow-up into primary care is likely to be a key future area for quality and cost-effective cancer care. Evidence from other solid cancer types demonstrates that such follow-up has no adverse outcomes, similar health-related quality of life, high patient satisfaction rates at a lower cost to the healthcare system. Core elements for successful models of shared cancer care are required: clear roles and responsibilities, timely effective communication, guidance on follow-up protocols and common treatments and rapid routes to (re)access specialist care. There is thus a need for improved communication between hospital specialists and primary care. Unmet needs for patients with early stage lung cancer are likely to include psychological symptoms and carer stress; the importance of smoking cessation may frequently be overlooked or underappreciated in the current hospital-based follow-up system. There is therefore a need for quality randomised controlled trials of patients with resected early stage lung cancer to establish optimal protocols for primary care-based follow-up and to more adequately address patients' and carers' unmet psychosocial needs, including the crucial role of smoking cessation.